Methodology of Teaching Energy Supply in Agriculture and Water Resources (National and Foreign Experience) (Texas Journal of Agriculture and Biological Sciences, 2022)
In the following article the methodics of teaching the issues of energy supplies in the agriculture and irrigation. The new innovational technologies of supply of energy are discussed. The proposals are given based on the scales of national and international experience